(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2012)
The author emphasizes the role of vocational adult education, reinforced in the current development of society by a large-scale scientific and technological revolution, economic development and the emergence of new technologies. Under review are the theoretical foundations and methodological features of in-house corporate training as a separate direction of adult education.